2015
DOI: 10.1515/bot-2015-0048
|View full text |Cite
|
Sign up to set email alerts
|

On the occurrence of three red algal species new to the Mediterranean Sea in Al-Hoceima National Park (Morocco)

Abstract: The occurrence in Morocco of three species of red algae new to the Mediterranean Sea is reported:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Its diaphragms have also 8-10 cells across axes segmented, beaded (below, with cystocarps), segments about as broad as long, filled with a watery mucilag. But, it is clearly distinguished from C. compressa by its cylindrical axes and branching pattern (Ballantine & Lozada Troche, 2008;N'Yeurt & Payri, 2010;Moussa et al, 2015). (Figure 3) This species, which was described from Klein Piscadera, Curacao, Netherlands Antilles (Van den Hoek, 1978), widely reported in the western coast of the Atlantic ocean and Pacific Islands (Guiry & Guiry, 2018), so that their presence in Morocco merely extends their range.…”
Section: Champia Compressa Harveymentioning
confidence: 99%
See 1 more Smart Citation
“…Its diaphragms have also 8-10 cells across axes segmented, beaded (below, with cystocarps), segments about as broad as long, filled with a watery mucilag. But, it is clearly distinguished from C. compressa by its cylindrical axes and branching pattern (Ballantine & Lozada Troche, 2008;N'Yeurt & Payri, 2010;Moussa et al, 2015). (Figure 3) This species, which was described from Klein Piscadera, Curacao, Netherlands Antilles (Van den Hoek, 1978), widely reported in the western coast of the Atlantic ocean and Pacific Islands (Guiry & Guiry, 2018), so that their presence in Morocco merely extends their range.…”
Section: Champia Compressa Harveymentioning
confidence: 99%
“…In general, the Moroccan coast remains poorly studied, if compared to other biogeographic regions. In recent years, there has been an increasing interest in its algal biodiversity (Riadi et al, 2013;Moussa et al, 2015;Salhi et al, 2016;Hassoun et al, 2014Hassoun et al, , 2016aHassoun et al, -b, 2018.…”
mentioning
confidence: 99%
“…Inventories began with that of Riadi and Kazzaz (1998), Riadi et al (2000) and Kazzaz and Riadi (2000), who assign to the country 455 taxa at specific and intraspecific level, this followed soon afterward by the publication of Benhissoune et al (2001;2002a, b; which were more detailed and confirmed 612 species and intraspecific taxa, 15 taxa excludenda and 35 taxa inquirenda of the benthic marine algal flora of Morocco. More recently, we added 23 species (Riadi et al 2011(Riadi et al , 2013Hassoun et al 2014;2015a, b, 2016Moussa et al 2015). Despite these advances, much work remains to be done on the marine benthic flora of Morocco as relatively few habitats have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%